The Paradox of Unemployment and Job Vacancies : Some Theories Confronted by Data - Skolnik, M.; Siddiqui, F. (Relations industrielles / Industrial Relations, 1976)
The purpose of this paper is to see just how well available data enable us to come to grips with the apparent paradox of simultaneous job vacancies and unemployment.